Risk Factors Associated With Cerebrovascular Accidents: A Cross- Sectional Study From Western Nepal - Silwal, Mahesh (Nepal Medical College Journal, 2025)
Cerebrovascular accident (CVA) is a leading cause of mortality and disability worldwide, with a particularly high burden in South Asia due to increasing prevalence of traditional cardiovascular risk factors. This study aimed to assess the association of risk factors and clinical profiles of ischemic and hemorrhagic CVA in a tertiary care center in Western Nepal. A cross-sectional observational study was conducted in the emergency department of Nepalgunj Medical College Teaching Hospital from August 2021 to July 2022. A total of 478 CVA patients were included through convenience sampling. Data on risk factors, clinical presentation, and outcomes were collected and analyzed using appropriate statistical methods. Among 478 patients, 238 (49.8%) had ischemic CVA and 240 (50.2%) had hemorrhagic CVA. Hypertension (68.0% vs. 76.0%; p=0.047) and alcohol consumption (33.0% vs. 58.0%; p<0.001) were significantly associated with hemorrhagic CVA, while smoking (73.0% vs. 51.0%; p<0.001) and dyslipidemia (51.0% vs. 40.0%; p=0.017) were more common in ischemic CVA. Common clinical features included arm weakness (70.3%), slurred speech (23.6%), and facial drooping (23.0%). Hemorrhagic CVA was significantly associated with loss of consciousness (p<0.001), higher median systolic blood pressure (160 vs. 140 mmHg; p<0.001), and lower mean GCS (10 vs. 13; p<0.001). Mortality was higher in hemorrhagic CVA (N=59; p<0.001), while 97.0% of ischemic stroke patients were discharged. Significant associations between specific risk factors and stroke subtypes were observed. Early identification and management of modifiable risk factors are crucial to reducing the burden and severity of CVA in Nepal.